Safety assessment and behavioral effects of Solanum guaraniticum leaf extract in rats (Brazilian Journal of Pharmaceutical Sciences, 2016)
Solanum guaraniticum is a medicinal plant traditionally used to treat gastric and liver diseases. However, there is no documented evidence corroborating its safety. The present study evaluated the potential toxicity of S. guaraniticum leaf extract after acute administration in rats. Single doses of the extract (1.250, 2.500, and 5.000 mg/kg) were administered by gavage, and the rats were then monitored for 48 h and/or 14 days. Mortality, acute signs of toxicity, and general activity in the open field test were assessed as well as hematological and biochemical parameters, enzymatic activity (δ-aminolevulinate dehydratase and acetylcholinesterase), and oxidative stress parameters (lipid peroxidation level, non-protein thiol content, tissue catalase activity, and serum ferrous reducing power). Phytochemical analysis was also performed by HPLC. The results showed that extract administration produced no deaths (LD50 >; 5,000 mg/kg), and no significant adverse effects regarding food consumption, body weight gain, gross pathology, or other parameters. However, the open field tests showed a decrease in spontaneous activity (crossing and rearing) mainly at 48 h after treatment. The results suggest that S. guaraniticum extract is not acutely toxic, but causes alterations in central nervous system activity.